(untitled) (mathematica didactica, 2009)
Mathematical theorems can be constructed and established in many different ways. In this text we present a system of options, in which the plurality of ways of constructing and establishing theorems is reduced to a few basic elements. The framework is based on terms of philosophical logic: abduction, deduction and induction. The options are exemplified by problems, which challenge students to discover and verify mathematical theorems. The pros and cons of the options are going to be discussed.